Comprehensive biometric index for fetal growth assessment - Sosa Olavarría, Alberto (2021)
Assessing fetal growth and its deviations is a challenge for the physician who uses ultrasound fetal biometry to estimate gestational age and fetal weight, sometimes resulting in a prediction that deviates from reality. Objective: To process the data provided by seven authors, applying an integral biometric index formula, to confirm the possibility of coincidence between all the data obtained. Methods: Processing of head circumference (CC), abdominal circumference (CA) and femur length (LF) measurements according to gestational age published by 7 authors, to calculate the biometric index using the formula [CAF= (CC + CA) - LF]. Results: Polynomial equations were obtained for each group of data separately and finally the global data, correlating the values of the index and gestational age, obtaining the curvilinear correlation coefficient, with R² = 0.99 (p < 0.05). Conclusions: The comprehensive fetal growth index is proposed as a tool to verify fetal growth through sequential evaluation, regardless of the origin and characteristics of the population under study.